PENGARUH FREE CASH FLOW, RETURN ON ASSETS, TOTAL ASSETS TURNOVER DAN SALES GROWTH TERHADAP DIVIDEND PAYOUT RATIO (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012) - Mardiyati, Umi; Nusrati, Destyarsah; Hamidah, Hamidah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
The purpose of this study is to know the effect of Free Cash Flow, Return On Assets, Total Assets Turnover, and Sales Growth on Manufacture Firm Dividend Payout Ratio Listed in Indonesia Stock Exchange Period 2008 - 2012. The sample of several companies on Manufacturer Firm listed on Indonesia Stock Exchange. The research model in this study using panel data analysis (unbalanced panel) with fixed effect approach. The empirical results show that ROA have positive and significant effect on DPR. As for, free cash flow, and TATO have negative significant effect on DPR, but sales growth have negative and not significant effect on DPR. Simultaneous test showed that free cash flow, return on assets, total assets turnover, and sales growth significant effect on dividend payout ratio. Keywords: Free Cash Flow, Return On Assets, Total Assets Turnover, Sales Growth, Dividend Payout Ratio